4(y+2)-2(1-y)-4y=0

Simple and best practice solution for 4(y+2)-2(1-y)-4y=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y+2)-2(1-y)-4y=0 equation:


Simplifying
4(y + 2) + -2(1 + -1y) + -4y = 0

Reorder the terms:
4(2 + y) + -2(1 + -1y) + -4y = 0
(2 * 4 + y * 4) + -2(1 + -1y) + -4y = 0
(8 + 4y) + -2(1 + -1y) + -4y = 0
8 + 4y + (1 * -2 + -1y * -2) + -4y = 0
8 + 4y + (-2 + 2y) + -4y = 0

Reorder the terms:
8 + -2 + 4y + 2y + -4y = 0

Combine like terms: 8 + -2 = 6
6 + 4y + 2y + -4y = 0

Combine like terms: 4y + 2y = 6y
6 + 6y + -4y = 0

Combine like terms: 6y + -4y = 2y
6 + 2y = 0

Solving
6 + 2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 2y = 0 + -6
2y = 0 + -6

Combine like terms: 0 + -6 = -6
2y = -6

Divide each side by '2'.
y = -3

Simplifying
y = -3

See similar equations:

| -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 | | 6x^3-5x^2+1=0 | | -3x-14+10x=-2 | | -6(v+7)=9v+48 | | 2(3x+8)+6(x-1)=-12 | | 5x-4+3x=6x+4(2-x) | | 8-5x=-29 | | (5n^2+11)-(3n^2+6)= |

Equations solver categories